Children of Malaysians help Earthquake Victims - Ahmad Zaid, Sulaiman
Some 200 children of Malaysians in North Palmerston, New Zealand did the country proud when they successfully staged a charity concert, “Road to Recovery Concert 2010” which went to that Malaysians remained to be a caring lot although they were abroad.